A constituição de saberes docentes para a educação inclusiva - Nascimento, Paulo Rogerio Barbosa do (2022)
This thesis deals with the constitution of teaching knowledge on school inclusion in face of the changes in school paradigms. The research question was: how do Basic Education teachers constitute, mobilize, and acquire teaching knowledge, and what is this knowledge when working in inclusive classrooms? The study stemmed from the epistemological premise of Schütz's (2018) Comprehensive Sociology, and consists of qualitative research based on the Hybrid Thematic Oral History method. It encouraged the participating teachers to narrate facts and events they have experienced, thereby enabling the researcher to analyze and interpret meanings and senses expressed and/or inferred in the narratives, while approximating them to the scientific literature. The narratives were provided by three female teachers with over ten years of experience in Inclusive Education in the first stage of Elementary School. The preliminary categories of theoretical reference were: a) senses and meanings of school/inclusion and exclusion; b) the paradigm of school inclusion and its pedagogical consequences; c) teachers' training and performance in the context of school inclusion; d) day-to-day teaching as a formative process; e) teaching experience as a formative process; and f) types of teaching knowledge. After the organization instructed by oral history methodology, according to Meihy (2002), data analysis and interpretation was performed along with an adaptation of Interpretive Content Analysis, according to Minayo et al. (2013). The teachers recognized the school as an important social referent with a distinctive structure, although they considered the sociocultural context to be unsettling in terms of its social meanings. Faced with the educational paradigm shift and without substantial training, the teachers experienced crises of teaching identity and therefore invested in self-training. Despite the initial shock and stuckness, they were reactive. Each day was experienced and understood as a potential path of subversion, creativity, and a space for the "arts of doing". The knowledge acquired by the teachers encompassed, on the one hand, the macro context—the need to understand the paradigm of school inclusion; the disabilities and their particularities; the interdisciplinary and multiprofessional actions; and the interaction with different class plans and various teaching approaches — and, on the other hand, the micro context — knowledge related to the production of teaching materials and the teacher's ability to anticipate issues that hinder the classes, which maximizes teaching and learning time. Furthermore, the current context strains the daily lives of teachers with constant class interruptions caused by the crises of students with disabilities. The teachers also report that they miss collaborative networked training in which experiences and case studies can be shared, discussed, and interpreted from different theoretical perspectives, in order to build the knowledge of teachers in a formative spiral.